Two‐State Folding of the Outer Membrane Protein X into a Lipid Bilayer Membrane. (29th January 2019) - Rath, Parthasarathi; Sharpe, Timothy; Kohl, Bastian; Hiller, Sebastian
Abstract: Folding and insertion of β‐barrel membrane proteins into native membranes is efficiently catalyzed by β‐barrel assembly machineries. Understanding this catalysis requires a detailed description of the corresponding uncatalyzed folding mechanisms, which however have so far remained largely unclear. Herein, the folding and membrane insertion of the E. coli outer membrane protein X (OmpX) into 1, 2‐didecanoyl‐sn‐glycero‐3‐phosphocholine (PC10:0) membranes is resolved at the atomic level. By combining four different experimental techniques, global folding kinetics were correlated with global and local hydrogen bond‐formation kinetics. Under a well‐defined reaction condition, these processes follow single‐exponential velocity laws, with rate constants identical within experimental error. The data thus establish, at atomic resolution, that OmpX folds and inserts into the lipid bilayer of PC10:0 liposomes by a two‐state mechanism. Abstract : Die Faltung und Membraninsertion des Außenmembranproteins X (OmpX) von E. coli in 1, 2‐Didecanoyl‐ sn ‐glycero‐3‐phosphocholin(PC10:0)‐Doppelschichten wurde durch Fluoreszenzspektroskopie sowie H‐D‐Austausch in Kombination mit Lösungs‐NMR‐Spektroskopie und MS untersucht. Unter definierten Reaktionsbedingungen wurden identische Geschwindigkeitskonstanten für die Faltung beobachtet, woraus ein Zwei‐Zustands‐Mechanismus für die Faltung und Insertion folgt.